STUDENTS’ UNDERSTANDING OF FUNDAMENTAL CONCEPTS OF MECHANICAL WAVE (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
Contrast to force and motion concepts, students’ difficulties related to physics concepts underlying mechanical wave propagation has getting less attention in physics education research. This study exposed common students’ difficulties in solving conceptual problems related to mechanical wave propagation. Subject consisted of 128 first-year students in physics department of UM, enrolling the Introductory Physics II in 2013/2014 academic year. Data was gathered using two-tier, multiple choices test with Confidence Scale Rating. The study concluded that some fundamental concepts of wave such as general mathematical representation of wave propagation, motion of medium particles, and the relationship of v = λf, were not well understood by most students; even many students hold misconceptions. The study suggested further research to explore the causes of student’s difficulties more outentically, for example, using think aloud or clinical interview methods.Kontras dengan topik gaya dan gerak, kesulitan siswa terkait konsep-konsep yang melandasi fenomena perambatan gelombang masih kurang mendapatkan perhatian para peneliti pendidikan fisika. Artikel ini mengangkat kesulitan umum yang dialami mahasiswa dalam memecahkan masalah konseptual terkait fenomena perambatan gelombang. Subjek penelitian terdiri atas 128 mahasiswa tahun pertama jurusan fisika UM yang mengikuti perkuliahan Fisika Dasar II tahun akademik 2013/2014. Analisis didasarkan pada jawaban mahasiswa terhadap soal pilihan ganda dan tingkat keyakinan mahasiswa terhadap ketepatan jawabannya. Penelitian menyimpulkan bahwa konsep-konsep fundamental yang meliputi representasi matematis tentang karakteristik umum gelombang berjalan, gerakan partikel medium saat dilewati gelombang, dan hubungan belum dipahami dengan baik oleh sebagian besar mahasiswa; bahkan banyak mahasiswa yang terindikasi mengalami miskonsepsi. Disarankan untuk dilakukan penelitian lanjutan untuk mengeksplorasi lebih dalam dan lebih otentik penyebab kesulitan tersebut, misalnya menggunakan teknik think aloud atau interview klinis.